Quando mais é menos, e menos é nada: o problema do letramento e a educação escolar - GOMES, Gisele Silva (Universidade Federal do Oeste do Pará, 2024)
This research has as its central question the problem of literacy, especially its implications for school education. It starts from the assumption that the conceptual broadening and the indiscriminate expansion of the application of the concept produced a diffuse and instrumental perception ofschool education and training. The thesis sustained by this research, which, everything leads one to believe is confirmed by the data gathered, is that literacy was incorporated and disseminated in the Brazilian academic and pedagogical universe disregarding the criticism and questioning of primitive terms, in function of an epistemological oscillation of the human sciences. What has been called literacy is based in diversified formation and learning conceptions that add a range of meanings that make literacy a fluid concept, flooded by dualities and nuances linked to functional conceptions that seek to develop abilities and competences. To pursue the goal established, it was first developed a critically considering of the founding axes of the concept as they came to be established in Brazil from the 1980s onwards and carrying out a survey of occurrences of literacy accompanied by specifiers, verifying its theoretical insertion and its field. The analysis demonstrates that, as it appears, broadly and confusingly, the concept of literacy disputes negatively with the very concept of education, emptying it. And, although it presents itself as a novelty and progressive character, in fact, it reproduces non-critical models of education, sometimes reinforcing the instrumental-pragmatic perspective, sometimes reverberating idealist liberal theses. It is concluded that the vulgarization of literacy and its application in school and non-school contexts (many ofwhich want to deny the importance of school education) does not contribute to Brazilian education.